1998
DOI: 10.1038/27666
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of chromatic tuning in macaque primary visual cortex

Abstract: The ability to distinguish colour from intensity variations is a difficult computational problem for the visual system because each of the three cone photoreceptor types absorb all wavelengths of light, although their peak sensitivities are at relatively short (S cones), medium (M cones), or long (L cones) wavelengths. The first stage in colour processing is the comparison of the outputs of different cone types by spectrally opponent neurons in the retina and upstream in the lateral geniculate nucleus. Some ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
131
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 23 publications
16
131
2
Order By: Relevance
“…In line with previous findings, our MEG-SAM results showed significant gamma band synchronization in occipitotemporal cortex. We found that visual ERS occurred as early as around 20-50 ms after stimulus onset, a time-range consistent with previous reports on short visual latencies using single neuron recordings (Luck et al, 1997;Cottaris & De Valois, 1998;Tovee et al, 1993) and MEG/EEG methods (Braeutigam et a., 2001;Seeck et al, 1997). Our finding of significant ERS in the occipitotemporal cortex including the fusiform face area is also consistent with fMRI findings on face processing (Yovel and Kanwisher, 2004;Haxby et al, 2001).…”
Section: Visual Areasupporting
confidence: 81%
“…In line with previous findings, our MEG-SAM results showed significant gamma band synchronization in occipitotemporal cortex. We found that visual ERS occurred as early as around 20-50 ms after stimulus onset, a time-range consistent with previous reports on short visual latencies using single neuron recordings (Luck et al, 1997;Cottaris & De Valois, 1998;Tovee et al, 1993) and MEG/EEG methods (Braeutigam et a., 2001;Seeck et al, 1997). Our finding of significant ERS in the occipitotemporal cortex including the fusiform face area is also consistent with fMRI findings on face processing (Yovel and Kanwisher, 2004;Haxby et al, 2001).…”
Section: Visual Areasupporting
confidence: 81%
“…The delay of the S-cone signal confirms the results of Cottaris and De Valois (1998) and provides a mechanism for the slightly longer reaction times to stimuli operating through the S-opponent versus L/M-opponent subsystems (Smithson and Mollon, 2004); moreover, the different timing of center and surround, coupled with the chromatically opponent rebound re- Figure 10. Spatiotemporal response of the cone inputs to a single cone-opponent neuron.…”
Section: Time Course Of the Response Of Cone-opponent Neuronssupporting
confidence: 58%
“…sponses (see below), likely accounts for the shifting color preferences over time of some neurons when they are tested with fullfield stimuli (Cottaris and De Valois, 1998). Finally, the timing differences of center and surround may help explain why doubleopponent neurons have been so resistant to study with drifting sine-wave gratings.…”
Section: Time Course Of the Response Of Cone-opponent Neuronsmentioning
confidence: 99%
“…Nonlinear color tuning has been documented in previous studies of V1 (Cottaris and DeValois 1998;DeValois et al 2000;Hanazawa et al 2000;Lennie et al 1990;Solomon et al 2004;Wachtler et al 2000). Modeling attempts, however, have focused on a restricted class of nonlinear models, that is: linear summation of cone inputs followed by a static nonlinearity (Eq.…”
Section: Relationship To Previous Studiesmentioning
confidence: 85%